PTU-074 Ulcerative Colitis: The Alpha-e-beta-7 Integrin Is Associated With A High Frequency Of Th17, Th1 And Th17/th1 Cd4 Lymphocytes. (9th June 2014) - Lamb, CA; Mansfield, JC; Tew, GW; Gibbons, D; Long, AK; Irving, PM; Deihl, L; Eastham Anderson, J; O'Boyle, G; Jones, DE; Hayday, A; Keir, M; et al.
Abstract : Introduction: T lymphocytes expressing the αEβ7 integrin are highly enriched within human intestinal epithelium and lamina propria. Studies exploring pathogenic or protective functions of αEβ7 expressing cells are lacking. Defining this phenotype is critical for our understanding of IBD pathogenesis and of translational importance with the development of etrolizumab, a humanised antibody specific to the β7 integrin that blocks α4β7:MAdCAM-1 and αEβ7:E-cadherin interactions. Methods: Lymphocytes within colonic biopsies from a total of 43 UC and 35 non-disease control patients were studied. Multi-colour FACS was optimised to determine surface and intracellular protein expression (CD45, CD3, CD4, CD8, αE, β7, CD161, IL-17A, TNFα, IFNγ and IL-10). qPCR was performed on TCRαβ+ lymphocytes, FACS sorted into CD4 + αEβ7+, CD4 + αEβ7-, CD8 + αEβ7+ and CD8 + αEβ7- prior to gene expression assay. Dual stain IHC for αE, plus CD3, CD4, CD8 and FOXP3 was performed using a Ventana Benchmark XT autostainer. Severity of UC was stratified using the Mayo endoscopic score for ulcerative colitis. Results: Ulcerative colitis was associated with a significantly increased frequency of T lymphocytes in the intestinal mucosa (p < 0.05). IHC revealed the highest expression of αE on CD4 and CD8 intraepithelial lymphocytes, although a substantial number of lamina propria lymphocytes also expressed this integrin. In UC, FACS demonstrated CD4 + αEβ7+ lymphocytes had a higher potential to produce the pro-inflammatory cytokines IFNγ(p < 0.01), TNFα(p < 0.001) and IL-17A(p < 0.0001) than CD4 + αEβ7- lymphocytes. In addition, a mean of 31.5% of the CD4 + αEβ7+ lymphocytes produced both IL-17A and IFNγ compared to a mean of only 7.7% in the CD4 + αEβ7- compartment (p < 0.001). IL-10 was not differentially expressed between CD4 + αEβ7+ and CD4 + αEβ7- lymphocytes in controls or UC, and a low frequency of αEβ7+FOXP3+ cells was observed by IHC. qPCR array confirmed higher mRNA levels of IFNγ(p < 0.001), TNFα(p < 0.01) and IL-17A(p < 0.01), and lower transcription of FOXP3 (p < 0.0001) in CD4 + αEβ7+ cells compared to CD4 + αEβ7- cells. Conclusion: αEβ7 expression was associated with an enrichment of pro-inflammatory Th17, Th1 and Th17/Th1 T lymphocytes, and not associated with a regulatory phenotype. These data suggest therapeutic interventions targeting αE expressing T cells and the αEβ7 integrin itself may be viable approaches for reducing aberrant inflammatory responses in UC. Disclosure of Interest: C. Lamb Grant/research support from: Genentech, J. Mansfield Grant/research support from: Genentech, G. Tew Employee of: Genentech, D. Gibbons Grant/research support from: Genentech, A. Long Grant/research support from: Genentech, P. Irving Grant/research support from: Genentech, L. Deihl Employee of: Genentech, J. Eastham Anderson Employee of: Genentech, G. O'Boyle Grant/research support from: Genentech, D. Jones Grant/research support from: Genentech, A. Hayday Grant/research support from: Genentech, M. Keir Employee of: Genentech, J. Egen Employee of: Genentech, J. Kirby Grant/research support from: Genentech.